2007
DOI: 10.1111/j.1365-2923.2007.02904.x
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for migration among medical students from Karachi

Abstract: CONTEXT The subject of economic migration among health care professionals has received intense attention. However, the aetiology of this migration has not been rigorously evaluated in Pakistan. Such knowledge can potentially influence health care and academic policies. Our current study proposes to quantify the relative contributions of various personal, professional and economic variables among final-year medical students in Karachi.METHODS A self-administered structured questionnaire using a 10-point scale w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
48
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 13 publications
12
48
1
2
Order By: Relevance
“…Other reasons included poor work environment and poor teaching of residents in domestic training institutions. 39 On the contrary, similar studies from another medical school in Pakistan and 4 medical colleges in Riyadh, Saudi Arabia demonstrated that most of the final year medical students preferred to work in their respective home countries. 3 A similar study done in Athens, Greece showed that most of the students considered overseas for advanced training.…”
Section: Rural) 22mentioning
confidence: 91%
“…Other reasons included poor work environment and poor teaching of residents in domestic training institutions. 39 On the contrary, similar studies from another medical school in Pakistan and 4 medical colleges in Riyadh, Saudi Arabia demonstrated that most of the final year medical students preferred to work in their respective home countries. 3 A similar study done in Athens, Greece showed that most of the students considered overseas for advanced training.…”
Section: Rural) 22mentioning
confidence: 91%
“…Syed et al found that medical students in Pakistan considered moving abroad because of poor remuneration and poor quality of training (i.e. push factors) [17]. Kaushik et al collected data on graduates of a medical school in India and found that better quality graduates (as defined by the number of awards they received) were more likely to migrate [18].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from India indicates that perceived greater professional opportunities drive many potential migrant physicians 26. Similarly, a survey in Pakistan indicated that low remuneration and poor training and work environment influenced potential migrant physicians 27. Finally, factors such as changing medical school curricula17 and the greater likelihood of graduates from higher quality institutions to migrate have also been examined quantitatively 28 29…”
Section: Introductionmentioning
confidence: 99%